Female Athlete Mental Fitness Scale (FAMFS): Preliminary Validation And Standardization Of An Outcome Measure For Mental Health Assessment Of Female Athletes Of India - Janvhi Singh; Dharmita Yogeshwar; Niketa Ahirwar; Anshul Garhpale; Manisha; Irish Jain; Vipin Kumar Chandraker; Arpit Kulshreshta (Adolescência e Saúde, 2026)
Background: Mental health plays a significant role in athletic performance and overall well-being. Female athletes are particularly vulnerable to psychological and physiological challenges such as anxiety, depression, sleep disturbances, eating-related concerns, and menstrual health issues. However, limited multidimensional assessment tools are available specifically for female athletes in the Indian population. Objective: To develop and evaluate the reliability of the Female Athlete Mental Fitness Scale (FAMFS), a multidimensional outcome measure designed to assess mental health-related factors among female athletes. Methods: This instrumental cross-sectional study included 120 female athletes aged 14–40 years who had participated in sports activities for at least two years. The FAMFS was developed through literature review and domain identification focusing on five components: anxiety, depression, sleep quality, eating disorders, and menstrual health. The scale consisted of items rated on a 4-point Likert scale. Reliability analysis was performed using Cronbach’s alpha and intraclass correlation coefficient (ICC). Results: The FAMFS demonstrated acceptable internal consistency with satisfactory reliability values. The multidimensional structure of the scale enabled comprehensive assessment of psychological and physiological factors influencing female athletes. The findings support the potential usefulness of FAMFS as a screening and assessment tool for mental fitness among female athletes. Conclusion: The Female Athlete Mental Fitness Scale (FAMFS) is a promising multidimensional tool for assessing mental health-related concerns in female athletes. The scale may help clinicians, physiotherapists, coaches, and sports professionals identify psychological and behavioral factors affecting athlete well-being and performance. Further studies with larger sample sizes and advanced psychometric evaluation are recommended to strengthen its validity and clinical applicability.